Data selection in the assessment of higher order thinking skills: focus on cognitive competency - Lajis, Adidah; Mohd Nor@Abdullah, Anis Fadzilah; Awang Mat, Tiliza; Nasir, Haidawati; Ab Aziz, Normaziah (IEEE, 2019)
This paper is discussing on the higher order thinking skills assessment focusing on cognitive competency via assisted assessment. The focus is on short free text answer for tertiary level of education. The hybrid approached has been employed in the assessment. The techniques are a combination of CNN-seq and information theory. CNN-seq concept is used to generate the pattern of the answer and the information theory is employed to generate the amount of knowledge and finally the mark will be calculated. Based on initial test on few data, it is found that this hybrid technique has produced encouraging result. Data selection is carefully done to ensure the questions are belonging to higher order thinking skills category. It is found that most of questions to test this level of skills not in the format of textual answer. Due to the difficulty getting the data, the full testing result is still due. The data collection is still in progress..